2022
DOI: 10.1038/s43705-022-00191-8
|View full text |Cite
|
Sign up to set email alerts
|

The one health perspective to improve environmental surveillance of zoonotic viruses: lessons from COVID-19 and outlook beyond

Abstract: The human population has doubled in the last 50 years from about 3.7 billion to approximately 7.8 billion. With this rapid expansion, more people live in close contact with wildlife, livestock, and pets, which in turn creates increasing opportunities for zoonotic diseases to pass between animals and people. At present an estimated 75% of all emerging virus-associated infectious diseases possess a zoonotic origin, and outbreaks of Zika, Ebola and COVID-19 in the past decade showed their huge disruptive potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…Environmental surveillance of wastewater samples combined with high-throughput genomic sequencing can be a particularly valuable tool to monitor the vast diversity of microbes and anti-microbial resistance genes (Leifels et al, 2022; Santiago-Rodriguez, 2022). Accumulating genomic data from environmental samples can serve three purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental surveillance of wastewater samples combined with high-throughput genomic sequencing can be a particularly valuable tool to monitor the vast diversity of microbes and anti-microbial resistance genes (Leifels et al, 2022; Santiago-Rodriguez, 2022). Accumulating genomic data from environmental samples can serve three purposes.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that around 75% of the emerging infectious diseases have a zoonotic origin and through the host-virus interactions analyses, rodents and bats are among the major reservoirs of zoonotic viruses [ 108 ]. In this work, numerous potentially zoonotic viruses were detected in wastewater in metro Detroit area.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond bacteria, zoonotic pathogens also include viruses ( e.g. , Hendra virus, influenza virus A) ( Leifels et al., 2022 ) and parasites (e.g., Trypanosoma cruzi and Toxoplasma gondii ) ( Weiss, 2008 ). These pathogens can reach humans through direct contact with food, water, or the environment ( Figure 1 ).…”
Section: Zoonoses and The Spread Of Antimicrobial Resistancementioning
confidence: 99%